From the Capitol to the Heartland: Analyzing Congressional Rhetoric and the "Flyover Country" Narrative - Phillip Ardoin (Journal of the Austrian Association for American Studies)
This study examines the evolution and strategic use of the term "flyover country" in US congressional rhetoric from 1995 to 2024. Initially a benign geographic descriptor, "flyover country" has transformed into a potent symbol of cultural and political identity, particularly among Republican members of Congress. Through a comprehensive analysis of congressional speeches, committee hearings, and constituent correspondence, this research identifies an increase in the use of flyover rhetoric, especially during the Trump era. The study reveals that "flyover" is employed to evoke a sense of victimhood and marginalization among rural constituents, highlighting perceived economic and cultural disenfranchisement by coastal elites. The findings underscore the adaptability of political language and its role in shaping and reflecting socio-political divides in the United States. This research contributes to a deeper understanding of the dynamics of congressional rhetoric and the cultural and political undercurrents that influence US-American identity and discourse.